Comparison of TIMI Flow in STEMI Patients With and Without Resolution on Reciprocal ST Segment Depression Obtaining Fibrinolytic Alteplase Therapy - Aldino Satria Adhitya; Harris Hasan; Refli Hasan; A. Afif Siregar; Zulfikri Mukhtar; Ali Nafiah Nasution (ACI (Acta Cardiologia Indonesiana), 2019)
Background: STEMI patients need revascularization to improve blood flow and myocardial reperfusion. Further information can be obtained from the ECG including infarct size and prognosis of STEMI patients. ST segment depression (STSD) in reciprocal leads isassociated with poorer prognosis. STEMI patients with STSD resolution have a better TIMI flow compared with no STSD resolution. The aim of this study was to look for TIMI flow for STEMI subjects who received fibrinolytic therapy with and without resolution of STSD shortly after fibrinolytic.Methods: This study is a prospective cohort study, in which 60 STEMI subjects, patients performed coronary angiography diagnostics to assess TIMI flow. The resolution on reciprocal STSD is defined as a decrease of 50% in the amount of reciprocal STSD in 90- minute after fibrinolytic therapy started.Results: Bivariate analysis showed that ejection fraction <40% with p = <0.001; QRS duration, p = <0.001; anterior STEMI with p = <0.001; are significant factors for STSD resolution. QRS Fragmentation with p = <0.001; STSD resolution with p = <0.001; ST elevation resolution with p = <0.001; are significant factors for TIMI Flow. In the TIMI Flow comparison with reciprocal STSD resolution; the resolution of reciprocal STSD has a better TIMI flow with OR 28 [(5.5-141.9), p = <0.001].Conclusion: There were differences in TIMI Flow in STEMI patients with reciprocal STSD resolution and without reciprocal STSD resolution who received fibrinolytic alteplase therapy, where STEMI patients with reciprocal STSD resolution had a better TIMI Flow compared with STEMI patients without reciprocal STSD resolution.